Association between pre–biopsy white blood cell count and prostate biopsy – related sepsis - Bulut, Suleyman (Cent European J Urol, 2015)
INTRODUCTION: Despite all preventive measures and improved biopsy techniques, serious, life–threatening complications of prostate biopsy, including sepsis, still exist. In the present study, in order to identify the risk factors that may be associated with sepsis development after prostate–biopsy, we aimed to analyze retrospectively the data of our patients who underwent transrectal ultrasound–guided prostate biopsy. MATERIAL AND METHODS: We retrospectively reviewed the data of 889 patients who underwent prostate biopsy at our clinic. We compared pre–biopsy parameters (age, prostate volume, white blood cell (WBC) count, fasting blood glucose, free and total prostate specific antigen levels) between patients who developed sepsis and those who were sepsis–free following prostate biopsy. RESULTS: 28 patients (3.1%) developed sepsis. Among the risk factors evaluated, only pre–biopsy WBC count was found to be a significant risk factor for biopsy–related sepsis. A 5.1 fold increase was detected in the risk for sepsis development, when the cut–off value of WBC was accepted as 11.165/μL, OR: 5.1 (95% CI: 2.3–11.5). The post–biopsy sepsis development rate in patients with pre–biopsy WBC count greater and less than 11.165/μL was 13.7% (n = 10) and 3% (n = 18) respectively. CONCLUSIONS: Patients with a pre–biopsy WBC count greater than 11.165/μL should be informed of the increased risk of developing post–biopsy sepsis.